(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Neoliberalism or the contemporary transition of the age-old globalization has trans formed the face of textile production and trade in Kano, Nigeria. This article provides statistical analysis of the scenario of Factory C, weaving department production capacity (2000–2015).deindustrialization encouraged by the worsening performance indicators in production encouraged by the adverse effects of neoliberalism in two and a half decades (1990–2015). The study compares the effects of the phenomenon from 1990 to 1999 when neoliberalism was entrenched and from 2000 to 2015 when Kano experienced an increase in textile trade relationships with China encouraged by the free movement of goods and improved communications. Information on production performance indicators and trend in employment and capacity utilization in three sampled factories were ana lyzed. Descriptive statistics was used to provide a clear picture of the behavior of loca tion parameters of the data. The research also employed trend analysis techniques by plotting the observed data of the workforce and production capacity against the years under review. The analyses showed that heavy damage was done to the industry by neo liberalism and increased China’s exports. Moreover, the results indicated that production was at its peak in the 1990s in terms of labor strength and production capacity. A decline in production was observed over the years as the workforce and capacity reduced to an appalling number when China occupied the Kano production space. This was from 2000 when liberalism became endemic and the textile factories in Kano suffered its impact. The competitive position open to the foreign textile industry challenges the opportunities open to Kano textile industry by globalization. Our study can be used as a benchmark by the policy makers to formulate a policy that can create the development of a comprehen sive and workable home grown strategy which will in the long run ensure mutual benefi cial interaction and build the system for a genuine win–win position.